Effects of Ownership Structure on the Performance of Listed Companies on the Ghana Stock Exchange - churchill, ransford quarmyne (Archives of Business Research, 2014)
Every business organisation has an important decision of making returns. This decision also affects its capital base and the decision of either going for equity financing or debt financing. The stock markets are widely viewed as important, if not essential, for the functioning of modern capitalist economies. In Ghana, a huge gap exists in literature on the impact of ownership structure and a firm performance as well as the measure of ownership structure and whether or not the endogeneity of ownership structure affect performances of firms. This paper therefore sought to determine the relationship between the ownership structure of listed firms and performance on Stock Market. The paper made used of secondary data and the data were analyzed using Pearson’s Product Moment Correlation and Logistic Regression. The first finding indicates that there is a significant negative relationship between ownership concentration and firm performance. The second finding shows a positive relationship between insider ownership and firm performance. The paper recommends that there is dire need to reasonably diversify shareholding as a way of attracting more skills and competencies among the shareholders that can be tapped to improve firm performance. At the same time, the managers should be protected from unnecessary direct interference by the shareholders.